2010
DOI: 10.1016/j.virol.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of genome segment 2 encoding RNA dependent RNA polymerase of Antheraea mylitta cytoplasmic polyhedrosis virus

Abstract: Genome segment 2 (S2) from Antheraea mylitta cypovirus (AmCPV) was converted into cDNA, cloned and sequenced. S2 consisted of 3798 nucleotides with a long ORF encoding a 1116 amino acid long protein (123 kDa). BLAST and phylogenetic analysis showed 29% sequence identity and close relatedness of AmCPV S2 with RNA dependent RNA polymerase (RdRp) of other insect cypoviruses, suggesting a common origin of all insect cypoviruses. The ORF of S2 was expressed as 123 kDa soluble His-tagged fusion protein in insect cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…We have previously characterized the structure of AmCPV by electron microscopy and its genome by electrophoresis which reveals that it is similar to that of a type- 4 CPV and consists of 11 ds RNA molecules [23]. We have also reported that the genome segments 6, 7, 8 of AmCPV encode viral structural proteins [24-26], segment 2 encodes viral RNA dependent RNA polymerase [27], segment 9 encodes a nonstructural protein, NSP38, having RNA binding property [28], segment 10 codes for polyhedrin [29] and segment 11 does not code for any protein [26]. But the genome segments encoding viral capsid proteins have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously characterized the structure of AmCPV by electron microscopy and its genome by electrophoresis which reveals that it is similar to that of a type- 4 CPV and consists of 11 ds RNA molecules [23]. We have also reported that the genome segments 6, 7, 8 of AmCPV encode viral structural proteins [24-26], segment 2 encodes viral RNA dependent RNA polymerase [27], segment 9 encodes a nonstructural protein, NSP38, having RNA binding property [28], segment 10 codes for polyhedrin [29] and segment 11 does not code for any protein [26]. But the genome segments encoding viral capsid proteins have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…All these genomic segments have been cloned, sequenced and characterized at the molecular level (Qanungo et al, 2000(Qanungo et al, , 2002Sinha-Dutta et al, 2005;Jangam et al, 2006;Chavali & Ghosh, 2007;Chavali et al, 2008;Chakrabarti et al, 2010;Ghorai et al, 2010;Biswas et al, 2014a, b). AmCPV is a member of the genus Cypovirus of the family Reoviridae, infecting Indian nonmulberry tasar silkworm Antheraea mylitta, and causes substantial economic loss each year (Jolly et al, 1974;Mertens et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…of~3.0 and incubated at 23 C. At 76 h post-infection, cells were harvested and purified P 123 was obtained as described by Ghorai et al (2010). Purified P 123 was finally stored in buffer containing 25 mM HEPES pH 7.5, 100 mM KCl, 50 mM NaCl and 10 % glycerol (v/v).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these genome segments except S4 and S5 have been cloned, sequenced, and functions of some of them have been determined. S1 and S3 code for viral capsid proteins [ 14 ], S2 codes for RNA dependent RNA polymerase [ 15 ], S6 codes for protein having ATP binding and ATPase activity [ 16 ], S7 and S8 encode viral structural proteins [ 17 , 18 ], S9 codes for a non-structural protein having RNA binding property [ 19 ]. S10 codes for viral polyhedron [ 20 ], and S11 does not contain any ORF [ 18 ].…”
Section: Introductionmentioning
confidence: 99%